Relationship between Birefringence and Surface Morphology in Single‐Crystal Diamonds Grown by MPCVD. Issue 7 (7th June 2018) - Zhao, Yun; Guo, Yanzhao; Lin, Liangzhen; Zheng, Yuting; Hei, Lifu; Liu, Jinlong; Wei, Junjun; Chen, Liangxian; Li, Chengming
Abstract: Single‐crystal diamonds are successfully synthesized using microwave plasma chemical vapor deposition. A smooth and flat single‐crystal surface is obtained by optimizing the size relationship between the seed substrate and the square hole of the shielding ring. When the sample grows higher than the polycrystalline diamond on the molybdenum holder, the surface becomes uneven. The polarization characteristics of two kinds of chemical vapor deposition (CVD) layers are compared between flat and uneven surfaces. Abnormal high‐order birefringence occurs in both morphologies, which is related to the dislocation density in the CVD layers. The higher the dislocation density of the sample, the more obvious the high‐order anomalous birefringence. High‐pressure high‐temperature seed substrates have obvious defects, such as dislocations, stacking faults, and boundaries of the growth sector, and these defects are mostly distributed at the edge of seed substrates. When the diamond surface demonstrates an edge‐to‐center morphology, the dislocations in the seed substrate, interface‐induced dislocations, and dislocations formed in the growth layer begin to converge toward the central region of the CVD layer, which results in a smaller area of low stress in the center of the CVD layer. High dislocation density causes the crystal to have a mosaic structure and orientation deviation. Abstract : Single‐crystal diamonds are successfully synthesized using microwave plasma chemical vapor deposition. A smooth and flat single‐crystal surface is obtained by optimizing the size relationship between the seed substrate and the square hole of the shielding ring. The higher the dislocation density of the sample, the more obvious the high‐order anomalous birefringence. High dislocation density causes the crystal to have an orientation deviation.